Insights into Kinetics of Methane Hydrate Formation in the Presence of Surfactants - Jyoti Shanker Pandey; Yousef Jouljamal Daas; Nicolas von Solms (Processes, 2019)
Sodium dodecyl sulfate (SDS) is a well-known surfactant, which can accelerate methane hydrate formation. In this work, methane hydrate formation kinetics were studied in the presence of SDS using a rocking cell apparatus in both temperature-ramping and isothermal modes. Ramping and isothermal experiments together suggest that SDS concentration plays a vital role in the formation kinetics of methane hydrate, both in terms of induction time and of final gas uptake. There is a trade-off between growth rate and gas uptake for the optimum SDS concentration, such that an increase in SDS concentration decreases the induction time but also decreases the gas storage capacity for a given volume. The experiments also confirm the potential use of the rocking cell for investigating hydrate promoters. It allows multiple systems to run in parallel at similar experimental temperature and pressure conditions, thus shortening the total experimentation time. Understanding methane hydrate formation and storage using SDS can facilitate large-scale applications such as natural gas storage and transportation.